PHONOSURGERY AND OTHER VOICE IMPROVEMENT TECHNIQUES - KACKER, SK (Med J Armed Forces India, 1997)
This paper records our experience in dealing with 432 patients where phonosurgery was done. The cadaver study of the larynx confirms the basic principles on which the techniques are based. Our experience with Type 1 thyroplasty is that it gives better results than Teflon paste injection. Use of the microscope during laryngeal surgery has given us greater precision in dealing with mucosal and submucosal pathology. The results of surgery are excellent but require to be followed up with vocal rest, hygiene and rehabilitation to prevent recurrence and get good long-term results of voice improvement.